Intermediality in Macedonian theatre - Петровска-Кузманова, Катерина (Poznańskie Studia Slawistyczne, 2012)
In the text Intermediality in Macedonian theatre, which uses the play Macedonian bloody wedding by Vojdan Chernodrinski, directed by Ljupco Gorgievski, as an example, an attempt is made at representing intermediality in theatrical performance. It is achieved through a ready-made technique in which a significant role is played by the music group Foltin and their performance. They use various props, which they turn into their instruments. This leads to their actualization through dedication to their essence. In this way, the old forms and elements of the traditional folk culture cross the bounds of time, reading the folklore signs in the style of the postmodern scene expressions.